1975
DOI: 10.1002/jcp.1040860118
|View full text |Cite
|
Sign up to set email alerts
|

ITP pyrophosphohydrolase and idp phosphohydrolase in rat tissue

Abstract: The existence of a nucleoside triphosphate pyrophosphohydrolase specific for ITP has been demonstrated in the cytosol fraction of a variety of rat tissues. The enzyme, stable to moderate heat treatment, was present in erythrocytes as well as brain, heart, kidney, liver, lung, muscle, ovaries, spleen, testes and thymus. The specific activity of the enzyme ranges from 26 to 150 mumoles/min/g protein. In addition, evidence is given for a heat labile nucleoside diphosphate (IDP) phosphohydrolase present in most ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The distribution of ITPA transcripts in human tissues agrees with the distribution of ITPase enzyme activity in different rat tissues (17). These and other studies also suggested that the enzyme was located in the cytoplasm (6,17). We have confirmed this location by transfection of COS-7 cells with a construct in which hITPase was fused to the C terminus of green fluorescent protein.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The distribution of ITPA transcripts in human tissues agrees with the distribution of ITPase enzyme activity in different rat tissues (17). These and other studies also suggested that the enzyme was located in the cytoplasm (6,17). We have confirmed this location by transfection of COS-7 cells with a construct in which hITPase was fused to the C terminus of green fluorescent protein.…”
Section: Discussionsupporting
confidence: 85%
“…The presence of hITPase mRNA in all human tissues examined and its high expression in endocrine glands was shown by Northern blot analysis and by cDNA microarray hybridization. The distribution of ITPA transcripts in human tissues agrees with the distribution of ITPase enzyme activity in different rat tissues (17). These and other studies also suggested that the enzyme was located in the cytoplasm (6,17).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Homologs of ITPA have been identified in all three domains of life. This includes the archaea Methanococcus jannaschii [26] and the bacteria E. coli [49], as well as the eukaryotes Saccharomyces cerevisiae [3, 75], mice [76], rats [77], rabbits [78], and humans [1]. These facts lead to the conclusion that the function of ITPA must be important.…”
Section: Problems Arising From Non-canonical Nucleotidesmentioning
confidence: 99%
“…ITP-ase is a nucleoside triphosphate pyrophosphohydrolase that is specific for ITP (Vanderheiden 1975). Vanderheiden (1969) reported high levels of ITP in the erythrocytes of two siblings and suggested that this resulted from homozygous deficiency of ITP-ase (MIM 147520).…”
mentioning
confidence: 99%